Effect of Techniques and Time of Sowing, Seed Rate, and Weed Management on Selcted Herbaceous Legumes Establishments in East Nusa Tenggara, Indonesia - Debora - KanaHau; Jacob Nulik (Jurnal Ilmu Ternak dan Veteriner, 2016)
A series of experiments on techniques and time of sowing, and weed management of legumes Clitoria ternatea cv Milgarra, Centrosema pascuorum cv Cavalcade and cv Bundey, and Lablab purpureus cv Highworth, was conducted in East Nusa Tenggara (in the islands of Timor, Flores, and Sumba) in order to determine proper technique and time of sowing and weed management, which would be efficient in labor use and sufficient biomass production. Treatments of sowing techniques included dibble, furrow (covered and not covered), and broadcast (harrowed and not harrowed); while sowing time consisted of early wet season (December-January), mid of wet season (February-March) and the end of wet season (April-May), while weed managements consisted of weeded and unweeded treatments. The experiments employed block randomized design with four replications using plot sizes of 3 x 4 m to 4 x 5 m, depending on the availability of land for the experiments. The results of the experiments showed that the best sowing technique with the highest plant population  at 4 weeks after planting was dibbling (42 plants/m²), followed by furrow, while the lowest plant population was obtained at the broadcast technique (9-20 plants/m²). Similarly, the highest biomass production was obtained in the dibbling technique (1.75 to 2.5 tons DM/ha per harvest at 12 weeks after planting in Ende, and 4-5 ton DM/ha in Nagekeo), followed by furrow technique covered or not covered (1-1.3 tons DM/ha in Ende and 3.5-4 tons DM/ha in Nagekeo), and the lowest in broadcast technique (0.3-1 ton DM/ha in Ende and 2-2.5 ton DM/ha in Nagekeo). However, considering the labor requirement and cost, it was recommended that furrow technique to suit the small farmer practices in the region. Weed management showed that weeded treatment (keep legume cleaned of weeds) gave significantly better (P<0.05) biomass production compared with to that of unweeded treatment. It can be seen also that weed had more suppressing effects on Clitoria ternatea, compared to that of Lablab purpureus, especially when the plants were sown in the early wet season.